Hydrodynamic Investigation of a Submarine Moving Under Free Surface - Dogrul, Ali (CHAMBER MARINE ENGINEERS, 2019)
Submerged bodies are commonly used in many fields such as scientific researches, military and commercial applications. Especially in military applications, submarines have a significant role as a silent and deterrent vehicle. Contrary to popular belief, submerged bodies also operate in shallow depth that free surface effects come into play. This causes the visual identification of submarines while protecting them from sonar detection. This study focuses on the investigation of free surface effects on submarine hydrodynamics moving forward in different depths. The numerical calculations have been conducted at different Reynolds numbers ranging from 1.5x10(7) to 3.5x10(7) for both bare and appended forms of DARPA Suboff. A commercial CFD solver has been used to solve URANS equations with k-epsilon turbulence model. The numerical approach has first been verified and validated with the available experimental data. Later, the numerical results have been discussed in terms of total resistance, resistance components and free surface deformations. It has been concluded that the submergence depth has a significant role on resistance components for depth Froude number larger than 0.7 and the appendages have little effect on free surface deformations in all depths.
Keywords: Appendage; CFD; DARPA; Free Surface; Resistance; CFD SIMULATIONS; UNDERWATER VEHICLE; SELF-PROPULSION; VERIFICATION; SUBMERGENCE; Engineering; Transportation